Happiness in the air: How does a dirty sky affect subjective well-being? - Zhang, Xin; Zhang, Xiaobo; Chen, Xi (International Food Policy Research Institute, 2015)
Existing studies that evaluate the impact of pollution on human beings understate its negative effect on cognition, mental health, and happiness. This paper attempts to fill in the gap via investigating the impact of air quality on subjective well-being using China as an example. By matching a unique longitudinal dataset at the individual level, which includes self-reported happiness and mental well-being measures, with contemporaneous local air quality and weather information according to the exact date and place of interview, we show that worse air quality reduces shorter-term hedonic happiness and increases the rate of depressive symptoms. However, life satisfaction, an evaluative measure of happiness, is largely immune from immediate bad air quality.